The broader benefits of vaccines: methodologies for inclusion in economic evaluation - Steven Simoens; Sandy Tubeuf; Nicolas Dauby; Olivier Ethgen; Sophie Marbaix; Marjan Willaert; Jeroen Luyten (Taylor & Francis Group, 2024)
Background As the societal value of vaccines is increasingly recognized, there is a need to examine methodological approaches that could be used to integrate these various benefits in the economic evaluation of a vaccine.Research design and methods A literature review and two expert panel meetings explored methodologies to value herd immunity, health spillover effects (beyond herd immunity), impact on antimicrobial resistance, productivity, and equity implications of vaccines.Results The consideration of broader benefits of vaccines in economic evaluation is complicated and necessitates technical expertise. Whereas methodologies to account for herd immunity and work productivity are relatively well established, approaches to investigate equity implications are developing and less frequently applied. Modeling the potential impact on antimicrobial resistance not only depends on the multi-faceted causal relationship between vaccination and resistance but also on data availability.Conclusions Different methods are available to value the broad impact of vaccines, and it is important that analysts are aware of their strengths and limitations and justify their choice of method. In the future, we expect that an increasing number of economic evaluations will consider the broader benefits of vaccines as part of their base-case analysis or in sensitivity analyses.